The historiographical Jesus: memory, typology, and the son of David - Le Donne, Anthony (Baylor University Press, 2009)
Introduction -- Hermeneutics and history -- History and memory -- Memory and typology -- Son of David and typology -- The therapeutic Son of David -- Excursus : the presupposition of Davidic descent -- Jesus' temple procession -- The Son of David question -- Concluding analysis